Evaluation of the Teacher Quality Improvement Training Program for Junior High School Level Using the CIPP Model - Usman Usman; Candra Wijaya; Muhammad Dalimunte (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study evaluates the Junior High School Teacher Quality Improvement Training Program organized by the Gayo Lues Department of Education using Stufflebeam’s CIPP (Context, Input, Process, Product) evaluation model to assess its relevance, implementation quality, and measurable outcomes. Methodology: Employing a qualitative evaluative design, the research involved teachers, principals, facilitators, and program organizers as key informants. Data were collected through in-depth interviews, direct observation, and documentation, and analyzed descriptively to capture the program’s effectiveness across the four CIPP dimensions. Main Findings: The findings show that the program is highly relevant to teachers’ professional development needs, particularly in strengthening pedagogical and classroom management skills. Although the program benefited from competent facilitators, input evaluation revealed shortcomings in learning facilities and teaching media. The process evaluation indicated that training sessions were generally well-implemented, yet participant engagement and reflective practice require improvement. The product evaluation demonstrated meaningful gains in teachers’ pedagogical competence; however, the transfer of training into classroom practice remained partial due to limited follow-up support. Novelty/Originality of this study: The novelty of this study lies in its comprehensive application of the CIPP model to a rural district training program, offering a nuanced diagnostic framework that links systemic constraints with individual teacher outcomes an approach seldom used in remote Indonesian contexts. The results highlight the need for active learning strategies, improved infrastructure, and structured post-training mentoring to sustain instructional improvements and ensure continuous professional growth among junior high school teachers.